(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2021)
The COVID-19 pandemic has created new landscapes and norms in the Malaysian society, including issues related to Muslims’ religious practices. Some of the practices affected include the postponement of the weekly Friday prayer, congregational prayers in mosques and suraus nationwide, and several other related matters. The fatwas made amidst a health crisis are in line with the legal view decided by the Special Muzakarah Committee of the National Council for Islamic Religious Affairs (MKI), which is supervised under the Department of Islamic Development Malaysia (JAKIM) and later overseen at the state level. The streamlining of fatwa issuance opens a new dimension to the standardisation and coordination of fatwas in Malaysia initiated by the decision, which has national significance, by the MKI. In contrast to previous practices, which position fatwas as the state’s exclusive right, efforts to standardise and coordinate fatwas faced constraints. This study seeks to answer whether fatwas are challenging to coordinate in Malaysia despite state laws’ provisions asserting that coordination can occur through the MKI and issues of national interests. This qualitative study uses document analysis for legal provisions that allow for coordination and standardisation. The findings of this study explain that the standardisation and coordination of fatwas are not strenuous to implement. The Syariah decisions regarding COVID-19 have had a considerable impact and have become a benchmark for further coordination and standardisation of other fatwas in Malaysia. Keywords: COVID-19, standardization and coordination of fatwas, MKI Muzakarah Committee, national interest